Sustainable Energy Access for Communities Rethinking the Energy Agenda for Cities - Fall, Aminata; Haas, Reinhard (Springer International Publishing : Imprint: Springer, 2022)
This open access book examines the transition to sustainable energy systems in emerging cities. Experts from around the world present case studies from different countries and discuss efforts were needed for achieving the United Nations Sustainable Development Goals (SDGs). The authors look into the issue of environment vs. economics and discuss the question of whether the energy transition goal can conflict with other development goals such as decent work and economic growth. Furthermore, innovation in energy transition is introduced, both in technology and citizens' engagement. The book presents the latest developments on energy access and transition to sustainability throughout the overall value chain: from basic research in universities to documentation of lessons learned in the field. The empirical evidence presented makes this book appealing to scholars in the field of energy sustainability as well as to policy-makers and energy service companies.